Assessment of heavy metals contamination and human health risk in shrimp collected from different farms and rivers at Khulna-Satkhira region, Bangladesh. (2016) - Sarkar, T.; Alam, M. Masihul; Parvin, N.; Fardous, Z.; Chowdhury, Alamgir Z.; Hossain, S.; Haque, M.E.; Biswas, N.
Abstract: This study is aimed to assess the heavy metals contamination and health risk in Shrimp ( Macrobrachium rosenbergii and Penaeus monodon ) collected from Khulna-Satkhira region in Bangladesh. The results showed that the Pb concentrations (0.52–1.16 mg/kg) in all shrimp samples of farms were higher than the recommended limit. The Cd levels (0.05–0.13 mg/kg) in all samples and Cr levels in all farms except tissue content at Satkhira farm were higher than the permissible limits. The individual concentration of Pb, Cd, and Cr between shrimp tissue and shell in all rivers and farms were not statistically significant (P > 0.05). Target hazard quotient (THQ) and hazard index (HI) were estimated to assess the non-carcinogenic health risks. Shrimp samples from all locations under the current study were found to be safe for consumption, the possibility of health risk associated with non-carcinogenic effect is very low for continuous consumption for 30 years.